2021
DOI: 10.1007/s43576-021-00031-0
|View full text |Cite
|
Sign up to set email alerts
|

Water Crimes and Governance: The Slovenian Perspective

Abstract: The demand for water is increasing due to its finite availability and a water-dependent world whose population is growing every day. It is important that there is not only enough water, but that the water is safe for human consumption and use in agriculture. Water crimes include various offences ranging from the pilfering of water from pipelines, to water pollution, to the illegal trafficking of water. These crimes are challenging to detect, investigate, and prosecute. This article presents a case study from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 29 publications
0
9
0
5
Order By: Relevance
“…22 Furthermore, as previously mentioned the practice of pollution may also represent a significant financial gain for the infringer, with evidence that some pollution actions are connected with organized crime. 8,9,11 Consequently, situations of reoccurrence and/or non-implementation of measures previously identified by the competent authorities as necessary to prevent situations of pollution of water resources are also important to be considered. Therefore, a correction is added to eqn (3), to include additional factors ( f add ) to include the above aspects:where f add is obtained as f add = 1 + ∑ f i …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…22 Furthermore, as previously mentioned the practice of pollution may also represent a significant financial gain for the infringer, with evidence that some pollution actions are connected with organized crime. 8,9,11 Consequently, situations of reoccurrence and/or non-implementation of measures previously identified by the competent authorities as necessary to prevent situations of pollution of water resources are also important to be considered. Therefore, a correction is added to eqn (3), to include additional factors ( f add ) to include the above aspects:where f add is obtained as f add = 1 + ∑ f i …”
Section: Methodsmentioning
confidence: 99%
“…A deeper analysis has shown that criminal networks usually involved in pollution crimes have been found to be connected to the, fraud, drugs, human trafficking, rearms trafficking or money laundering. 8,9,11 Water crimes include various offences ranging from the pilfering of water from pipelines, to water pollution, to the illegal trafficking of water. These crimes are challenging to detect, investigate, and prosecute.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations